PH salival y su relación con la enfermedad periodontal. Revisión de la literatura (2020)
The salivary pH plays a fundamental role in the maintenance of the tissues of the oral cavity and is of great importance when contributing to the conservation, maintenance and care of the same, The correct functioning of saliva will maintain a harmony in the mouth and the imbalances of salivary values are related to increased risk of caries or periodontal disease. Materials and methods: For the present study, a review of the literature was made of 60 articles related to salivary ph in patients with periodontal disease, changes in pregnant women and effects on oral rinses, published from 2001 to 2019 the search was carried out the following platforms as Pubmed, Science Direct, Google Academic, SciELO, Elsevier, database of antonio Nariño University. Results: It is determined that if there is a relationship between salivary pH and periodontal disease since elevated alkalinity levels were demonstrated in patients with large periodontal disease, this also shows that it depends on the increase of periodontal disease progression. Conclusion: Salivary pH has more alkaline values in patients with periodontal disease, in relation to healthy patients. Salivary pH values are also higher in periodontitis than in gingivitis. As the progression and spread of periodontal disease increase salivary pH presents a scale of greater alkalinity.